2014
DOI: 10.1007/s00394-014-0796-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in micronucleus frequency and acrylamide adduct levels with hemoglobin between vegetarians and non-vegetarians

Abstract: These data suggest that the vegetarian diet might be beneficial in lowering genomic instability in healthy individuals. The measured Hb adduct levels indicate that the total intake of acrylamide does not differ between the two studied groups and does not contribute to the observed difference in fMN, although an influence of the diet on the metabolic rates of acrylamide was indicated. In addition, the observed significant difference in the background fMN in the two groups demonstrated that the MN analysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
1
11
0
2
Order By: Relevance
“…The mechanism by which BMI may influence acrylamide metabolism is still unclear, but similar to the present study, other studies have observed that BMI was positively associated with the ratio HbGA/HbAA, and negatively associated with HbAA [14, 37, 38]. Recently, statistically significant differences in the ratio of HbGA/HbAA between vegetarians and non-vegetarians have been reported, suggesting that dietary factors may also contribute to acrylamide/glycidamide metabolism [39]. …”
Section: Discussionsupporting
confidence: 80%
“…The mechanism by which BMI may influence acrylamide metabolism is still unclear, but similar to the present study, other studies have observed that BMI was positively associated with the ratio HbGA/HbAA, and negatively associated with HbAA [14, 37, 38]. Recently, statistically significant differences in the ratio of HbGA/HbAA between vegetarians and non-vegetarians have been reported, suggesting that dietary factors may also contribute to acrylamide/glycidamide metabolism [39]. …”
Section: Discussionsupporting
confidence: 80%
“…Boxes, Perc 25/75; whisker, standard deviation; black squares, mean; dash, median; times symbol, minimum; asterisk, maximum; n.q. not quantified (due to no permission) blood reticulocytes of vegetarians (defined by excluding meat and fish from their diet) as compared to non-vegetarians, no significant difference in mean Hb adduct levels of AA and GA were found (Kotova et al 2015). The methodology applied in that study is, however, not comparable to our approach.…”
Section: Discussionmentioning
confidence: 79%
“…In the 20th century, cancer incidence (after correction for age) has increased worldwide (534)(535)(536) in parallel with the spread of western technology, pollution and consumer products (181,182,537) and some cancers can be regarded as diseases of affluence. Lifestyle factors including diet, smoking and lack of exercise probably contribute importantly to the risk of cancer in a large part of the population of the more developed countries, but exposure to carcinogens or co-carcinogens present in polluted air and drinking water, as well as in food, is also thought to contribute significantly.…”
Section: Discussionmentioning
confidence: 99%